Effectiveness of Rewards, Motivation, and Emotional Intelligence in Improving Employee Performance - Nengsi Sudirman; Muh. Ramli; Safri Tahir; Junaedi Arifin (Pustaka Digital Indonesia, 2025)
This study aims to analyze the influence of rewards, motivation, and emotional intelligence on employee performance. The independent variables studied include rewards (financial and non-financial rewards), motivation (internal and external motivation), and emotional intelligence (the ability to recognize and manage emotions). This study uses a quantitative approach with a survey method involving 50 employees from various divisions as respondents. The data were analyzed using multiple linear regression. The results showed that rewards, motivation, and emotional intelligence partially and simultaneously have a positive and significant effect on employee performance. The motivation variable has the greatest influence with a β coefficient value of 0.420, followed by rewards with a β of 0.350, and emotional intelligence with a β of 0.300. This shows that appropriate rewards, strong motivation, and the ability to manage emotions effectively can increase employee productivity and work quality. The findings of this study provide practicality for organizational management to take policies that pay attention to these three factors in order to improve employee performance. Emotional intelligence development programs, fair reward provisions, and work motivation improvement strategies need to be considered in human resource management. This study also recommends further research by considering moderating and mediating variables to obtain more comprehensive results.